Analisis Orientasi dan Penempatan Staf Operasional dalam Penanganan Keterlambatan Penerbangan: (Studi Kasus Super Air Jet) - Hilma Harmen; Santa Oktavia Turnip; Stepanny Lumban Gaol; Da Kezia Eriani Saragih; Clara Citra Sinaga (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Flight delays are one of the operational problems that frequently occur in the aviation industry and can affect service quality and passenger satisfaction. These conditions require effective operational coordination and adequate human resource readiness. One case that attracted public attention occurred at Super Air Jet, where a flight delay of several hours triggered passenger protests and resulted in an incident in which passengers were left behind when the aircraft departed. This incident indicates potential problems in human resource management, particularly related to employee orientation and the placement of operational staff. This study aims to analyze the role of employee orientation and the placement of operational staff in handling flight delays at Super Air Jet. The research method used is a qualitative method with a case study approach that utilizes secondary data in the form of scientific literature and mass media reports as research sources. The results show that adequate employee orientation and appropriate placement of operational staff play an important role in supporting effective operational coordination, delivering information to passengers, and handling flight delay situations. Therefore, proper human resource management through orientation programs and appropriate staff placement can help improve service quality and minimize operational errors in flight operations.